Zinc ion battery cathode material and preparation method and application thereof
By covering the surface of nickel metal organic frame nanosheets, an efficient zinc ion battery cathode material is prepared, which solves the problem of insufficient electrochemical performance of existing materials and achieves higher circulation capacity and Coulomb efficiency.
Patent Information
- Application Number
- CN202411841918.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-11
AI Technical Summary
The electrochemical properties of existing zinc ion battery cathode materials do not meet the needs of human development, especially in terms of cycle performance and Coulomb efficiency.
Nickel metal organic frame nanosheets are used as the base material and the surface is coated with transition metals, such as Cr, Zn, Co, Cu, Fe or Mn, to prepare efficient zinc ion battery cathode material through solvent thermal substitution reaction.
The first-circulation capacity and Coulomb efficiency of the cathode material of zinc ion battery are improved, and its circulation performance is enhanced, making it more suitable for electrochemical energy storage.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material preparation, in particular to a zinc ion battery cathode material and a preparation method and application thereof. Background Art
[0002] The energy crisis is a major problem facing contemporary mankind, which involves the rational use and storage of energy. In order to reasonably store energy, people have developed various electrochemical energy sources, including lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, multivalent ion batteries, etc. Among them, zinc-ion batteries have attracted widespread attention due to their high theoretical capacity, high safety and low cost. In order to increase the capacity of zinc-ion batteries, many transition metal-based battery materials have been developed, such as manganese-based materials, vanadium-based materials, etc.
[0003] Metal-organic frameworks are network-structured crystals formed by the coordination of metal ions or metal clusters with organic ligands, also known as porous coordination polymers. Their remarkable structural characteristics, such as low mass density, large pore volume, and rich porosity, determine that metal-organic frameworks have received widespread attention in the field of energy storage. Compared with bulk metal-organic frameworks, metal-organic framework nanosheets expose a huge specific surface area, which greatly improves the capacity of zinc-ion batteries. According to the journal Advanced Energy Materials, Vol. 8, 2018, No. 1802052, the synthesized ultrathin electrometallic metal-organic framework nanosheets exhibit good electrochemical performance in lithium-sulfur batteries. However, the efficiency of current metal-organic framework nanosheets as cathodes of zinc-ion batteries still does not meet the needs of human development. On the other hand, bimetallic metal-organic framework nanosheets have been found to have great potential in stability and their bimetallic active sites compared to single metals. How to develop a large-scale preparation method for bimetallic metal-organic framework materials, construct a stable heterogeneous interface, and further improve their electrochemical performance as cathode materials is an important issue in the field of electrical storage. Summary of the invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide a zinc ion battery cathode material and a preparation method and application thereof. The zinc ion battery cathode material provided by the present invention has a high first cycle capacity and coulombic efficiency and good cycle performance.
[0005] The present invention provides a zinc ion battery cathode material, which comprises a nickel metal organic framework nanosheet and a transition metal coated on the nickel metal organic framework nanosheet;
[0006] The transition metal is selected from one or more of Cr, Zn, Co, Cu, Fe or Mn.
[0007] The zinc ion battery cathode material provided by the present invention comprises a nickel metal organic framework nanosheet, wherein the nickel metal organic framework nanosheet is a Ni MOF nanosheet, and the ligand of the Ni MOF nanosheet is a carboxylic acid-containing ligand. In certain embodiments of the present invention, the carboxylic acid-containing ligand is a terephthalic acid ligand.
[0008] The zinc ion battery cathode material provided by the present invention further comprises a transition metal coated on the nickel metal organic framework nanosheet, wherein the transition metal is selected from one or more of Cr, Zn, Co, Cu, Fe or Mn. Preferably, the transition metal is selected from one of Co, Cu or Fe. Most preferably, the transition metal is selected from Co, and the strong hybridization characteristics of the Co 3d orbital and the O 2p orbital distort the electronic structure of Ni, thereby improving the redox activity of the active site.
[0009] The zinc ion battery cathode material provided by the present invention comprises a nickel metal organic framework nanosheet and a transition metal coated on the nickel metal organic framework nanosheet. The coated structure has a flexible electronic structure and a unique synergistic effect at the interface between the nickel metal organic framework nanosheet and the transition metal, which is beneficial to the electrical performance of the cathode of the zinc ion battery. The molar ratio of nickel to the transition metal in the nickel metal organic framework nanosheet of the present invention is (0.5-10):1.
[0010] The zinc ion battery cathode material provided by the present invention is a metal organic framework heterogeneous nanomaterial, specifically a metal organic framework heterogeneous nanosheet, with an average particle size of 2 μm to 3 μm and an average thickness of 1 nm to 5 nm. The zinc ion battery cathode material provided by the present invention is highly dispersed, uniform in size and thickness, which is conducive to the electrical performance of the zinc ion battery cathode.
[0011] The present invention also provides a method for preparing the above-mentioned zinc ion battery cathode material, comprising the following steps: heating a soluble transition metal salt, a nickel metal organic framework nanosheet, N,N-dimethylformamide and an alcohol to react to obtain the zinc ion battery cathode material.
[0012] The present invention uses two-dimensional metal organic framework nanosheets as templates and inducers to induce synthesis to obtain metal organic framework heterogeneous nanosheets, and the metal organic framework heterogeneous nanosheets are the above-mentioned zinc ion battery cathode materials. This method does not require complex equipment, the experimental operation is simple, and it is easy to prepare in large quantities. Specifically, a soluble transition metal salt, a nickel metal organic framework nanosheet, N, N-dimethylformamide and an alcohol are stirred for 8 min to 15 min to mix evenly to form a reaction solution, and a heating reaction is performed to obtain a zinc ion battery cathode material. In certain embodiments of the present invention, a soluble transition metal salt, a nickel metal organic framework nanosheet, N, N-dimethylformamide and an alcohol are placed in a reactor, stirred for 8 min to 15 min to mix evenly to form a reaction solution, and the reactor containing the reaction solution is sealed and heated to react to obtain a zinc ion battery cathode material.
[0013] The soluble transition metal salt of the present invention is selected from one or more of soluble Cr salts, soluble Zn salts, soluble Co salts, soluble Cu salts, soluble Fe salts or soluble Mn salts. Preferably, the soluble transition metal salt is selected from one of soluble Co salts, soluble Cu salts or soluble Fe salts. Most preferably, the soluble transition metal salt is selected from soluble Co salts. The anions of the soluble transition metal salt of the present invention include but are not limited to one or more of nitrate, chloride, sulfate, carbonate and acetate. In certain embodiments of the present invention, the soluble transition metal salt is selected from one or more of cobalt acetate, copper acetate monohydrate, ferric chloride heptahydrate or manganese acetate tetrahydrate, preferably selected from one of cobalt acetate, copper acetate monohydrate or ferric chloride heptahydrate, and most preferably selected from cobalt acetate.
[0014] The nickel metal organic framework nanosheet of the present invention is a Ni MOF nanosheet, and the ligand of the Ni MOF nanosheet is a carboxylic acid-containing ligand. The nickel metal organic framework nanosheet of the present invention is prepared from a nickel source and a carboxylic acid-containing ligand, specifically comprising the following steps: a nickel source, a carboxylic acid-containing ligand, water and N,N-dimethylacetamide react at 140° C. to 160° C. for 2.5 h to 3.5 h to obtain a nickel metal organic framework nanosheet. In certain embodiments of the present invention, the carboxylic acid-containing ligand is a terephthalic acid ligand.
[0015] The alcohol of the present invention is selected from one or more of ethanol, methanol, and acetonitrile, preferably ethanol. The molar ratio of nickel in the nickel organic metal framework nanosheet of the present invention to the transition metal in the soluble transition metal salt is (0.5-10):1, preferably (1-4):1; the volume ratio of N,N-dimethylformamide to alcohol is (1-10):1, preferably (2-5):1; the concentration of the nickel metal organic framework nanosheet is 0.3 mg / mL-3 mg / mL, preferably 0.5 mg / mL-1 mg / mL.
[0016] The heating reaction of the present invention is a solvent thermal substitution reaction, the temperature of the heating reaction is 50°C to 260°C, and the time of the heating reaction is 0.5 h to 50 h. Preferably, the temperature of the heating reaction is 100°C to 190°C, and the time of the heating reaction is 2 h to 20 h. More preferably, the temperature of the heating reaction is 120°C to 170°C, and the time of the heating reaction is 2 h to 10 h.
[0017] After the heating reaction, the present invention further comprises collecting the product obtained after the heating reaction, washing with water, washing with alcohol, and drying to obtain a zinc ion battery cathode material. The number of water washings in the present invention is 1 to 3 times; the number of alcohol washings is 1 to 3 times; the drying is room temperature drying, and the drying time is 5 hours to 24 hours. Preferably, the number of water washings is 1 to 2 times; the number of alcohol washings is 2 to 3 times; and the drying time is 8 hours to 20 hours.
[0018] The present invention also provides the use of the zinc ion battery cathode material described in any of the above technical solutions or the zinc ion battery cathode material obtained by the preparation method described in any of the above technical solutions in zinc ion battery energy storage. Specifically, the present invention provides a cathode, which includes a current collector and an active component arranged on the current collector; the active component is the zinc ion battery cathode material described in any of the above technical solutions or the zinc ion battery cathode material obtained by the preparation method described in any of the above technical solutions. The present invention also provides a zinc ion battery, which includes a cathode, an anode and an electrolyte; the cathode is the above-mentioned cathode.
[0019] The present invention provides a zinc ion battery cathode material, a preparation method and an application thereof. The zinc ion battery cathode material provided by the present invention has a uniform shape and size, has a high first cycle capacity and coulombic efficiency, and has good cycle performance. The preparation method of the zinc ion battery cathode material provided by the present invention can prepare bimetallic metal organic framework heterogeneous nanosheet materials with different doping contents by adjusting the concentration of transition metal ions, and changes the activity and stability of the material by changing the type of transition metal ions. The preparation method of the present invention is also conducive to large-scale preparation. This method does not require complex equipment, has simple experimental operations, and is easy to prepare in large quantities. The zinc ion battery cathode material provided by the present invention has important applications in electrochemical energy storage, and helps to improve the electrochemical performance of various types of battery electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope photograph of the cobalt-nickel metal organic framework heterogeneous nanosheet prepared in Example 1 of the present invention;
[0021] Figure 2The X-ray diffraction pattern of the cobalt-nickel metal organic framework heterostructure nanosheet prepared in Example 1 of the present invention;
[0022] Figure 3 The cobalt-nickel metal organic framework heterostructure nanosheet prepared in Example 1 of the present invention is used as a cathode material for a zinc ion battery when the current density is 4 A cm -2 Cycle performance diagram when
[0023] Figure 4 This is a scanning electron microscope photograph of the nickel-copper metal organic framework heterogeneous nanosheet prepared in Example 2 of the present invention;
[0024] Figure 5 The X-ray diffraction pattern of the nickel-copper metal organic framework heterostructure nanosheet prepared in Example 2 of the present invention;
[0025] Figure 6 The nickel-copper metal organic framework heterostructure nanosheet prepared in Example 2 of the present invention is used as the cathode material of the zinc ion battery when the current density is 4 A cm -2 Cycle performance diagram when
[0026] Figure 7 This is a scanning electron microscope photograph of the iron-nickel metal organic framework heterogeneous nanosheet prepared in Example 3 of the present invention;
[0027] Figure 8 The X-ray diffraction pattern of the iron-nickel metal organic framework heterostructure nanosheet prepared in Example 3 of the present invention;
[0028] Fig. 9 The iron-nickel metal organic framework heterostructure nanosheet prepared in Example 3 of the present invention is used as the cathode material of the zinc ion battery when the current density is 4 A cm -2 Cycle performance diagram when
[0029] Fig.10 This is a scanning electron microscope photograph of the manganese-nickel metal organic framework heterogeneous nanosheet prepared in Example 4 of the present invention;
[0030] Fig.11 The X-ray diffraction pattern of the manganese-nickel metal organic framework heterostructure nanosheet prepared in Example 4 of the present invention;
[0031] Fig.12 The manganese-nickel metal organic framework heterostructure nanosheet prepared in Example 4 of the present invention is used as a cathode material for a zinc ion battery when the current density is 4 A cm -2 Cycle performance diagram when . DETAILED DESCRIPTION
[0032] The present invention discloses a zinc ion battery cathode material and a preparation method and application thereof. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0033] The drugs and reagents used in the experiment were purchased from Sinopharm Chemical Reagent Co., Ltd., and the hydrothermal closed reaction vessel was a stainless steel reactor produced by Fujian Shengxin Machinery Co., Ltd.
[0034] The metal organic framework nanosheets used in this experiment are Ni MOF, which is prepared by heating a mixed reaction solution of 0.0620 g nickel acetate tetrahydrate, 0.0207 g terephthalic acid, 15 ml water and 15 ml N,N-dimethylacetamide at 150 °C for 3 hours. After cooling to room temperature, centrifugation, washing with water once, washing with ethanol twice, and drying at 60 °C for 8 hours.
[0035] The present invention will be further described below in conjunction with embodiments:
[0036] Example 1
[0037] Preparation of NiCoMOF heterogeneous nanosheets:
[0038] 25 mg Ni MOF, 10 mg cobalt acetate, 24 mL N,N-dimethylformamide, and 8 mL ethanol were placed in a 50 mL reactor. After stirring on a magnetic stirrer for 10 min, it was sealed and placed in an oven at 150 °C for heating to carry out a solution thermal substitution reaction for 3 h. The obtained product was washed once with water, twice with alcohol, and then dried.
[0039] The cobalt-nickel metal organic framework heterogeneous nanosheets prepared in Example 1 of the present invention were characterized in terms of morphology, phase and electrochemistry. Figure 1 , Figure 1 This is a scanning electron microscope photo of the cobalt-nickel metal organic framework heterogeneous nanosheet prepared in Example 1 of the present invention. Figure 1 It can be seen that the size and thickness of the prepared CoNi metal-organic framework nanosheets are very uniform. Figure 2 , Figure 2 This is the X-ray diffraction pattern of the cobalt-nickel metal organic framework heterostructure nanosheet prepared in Example 1 of the present invention. It can be seen that the diffraction peak of the prepared product is significantly offset compared with that of Ni MOF. Figure 3 , Figure 3The cobalt-nickel metal organic framework heterostructure nanosheet prepared in Example 1 of the present invention is used as a cathode material for a zinc ion battery when the current density is 4 A cm -2 The cycle performance diagram shows that the capacity of the prepared CoNi metal organic framework heterostructure nanosheet electrode can reach 0.2440 mAh cm in the first cycle. -2 The coulombic efficiency can reach 89.1%, and the capacity can still reach 0.1620 mAh cm after 600 cycles. -2 .
[0040] Example 2
[0041] Preparation of NiCuMOF nanosheets:
[0042] 25 mg Ni-MOF, 10 mg copper acetate monohydrate, 24 mL N,N-dimethylformamide, and 8 mL ethanol were placed in a 50 mL reactor. After stirring on a magnetic stirrer for 10 min, it was sealed and heated in an oven at 150 °C for a solvothermal substitution reaction for 3 h. The obtained product was washed once with water, twice with alcohol, and then dried.
[0043] The nickel-copper metal organic framework heterogeneous nanosheets prepared in Example 4 of the present invention were characterized in terms of morphology, phase and electrochemistry. Figure 4 , Figure 4 This is a scanning electron microscope photo of the nickel-copper metal organic framework heterogeneous nanosheet prepared in Example 2 of the present invention. Figure 4 It can be seen that the size and thickness of the prepared NiCuMOF heterostructure nanosheets are very uniform. Figure 5 , Figure 5 This is the X-ray diffraction pattern of the nickel-copper metal organic framework heterostructure nanosheet prepared in Example 2 of the present invention. It can be seen that the diffraction peak of the prepared product is significantly offset compared with that of Ni MOF. Figure 6 , Figure 6 The nickel-copper metal organic framework heterostructure nanosheet prepared in Example 2 of the present invention is used as the cathode material of the zinc ion battery when the current density is 4 A cm -2 The cycling performance diagram of the prepared nickel-copper metal organic framework heterostructure nanosheet electrode can reach a capacity of 0.2062 mAh cm in the first cycle. -2 The coulombic efficiency can reach 67.4%, and the capacity can still reach 0.1310 mAh cm after 999 cycles. -2 .
[0044] Example 3
[0045] Preparation of Fe-Ni MOF nanosheets:
[0046] 25 mg Ni-MOF, 10 mg ferric chloride heptahydrate, 24 mL N,N-dimethylformamide, and 8 mL ethanol were placed in a 50 mL reactor. After stirring on a magnetic stirrer for 10 min, it was sealed and placed in an oven at 150 °C for heating to carry out a solvothermal substitution reaction for 3 h. The obtained product was washed once with water, twice with alcohol, and then dried.
[0047] The iron-nickel metal organic framework heterogeneous nanosheets prepared in Example 3 of the present invention were characterized in terms of morphology, phase and electrochemistry. Figure 7 , Figure 7 This is a scanning electron microscope photo of the Fe-Ni metal organic framework heterogeneous nanosheet prepared in Example 3 of the present invention. Figure 7 It can be seen that the size and thickness of the prepared Fe-Ni metal-organic framework nanosheets are very uniform. Figure 8 , Figure 8 This is the X-ray diffraction pattern of the Fe-Ni metal organic framework heterostructure nanosheet prepared in Example 3 of the present invention. It can be seen that the diffraction peak of the prepared product is significantly offset compared with that of Ni MOF. Fig. 9 , Fig. 9 The iron-nickel metal organic framework heterostructure nanosheet prepared in Example 3 of the present invention is used as the cathode material of the zinc ion battery when the current density is 4 A cm -2 The cycling performance diagram shows that the capacity of the prepared Fe-Ni metal organic framework nanosheet electrode can reach 0.1171 mAh cm in the first cycle. -2 The coulombic efficiency can reach 86.7%, and the capacity is 0.0553 mAh cm after 600 cycles. -2 .
[0048] Example 4
[0049] Preparation of Mn-Ni Metal-Organic Framework Nanosheets:
[0050] 25 mg Ni-MOF, 10 mg manganese acetate tetrahydrate, 24 mL N,N-dimethylformamide, and 8 mL ethanol were placed in a 50 mL reactor. After stirring on a magnetic stirrer for 10 min, it was sealed and placed in an oven at 150 °C for heating to carry out a solvothermal substitution reaction for 3 h. The obtained product was washed once with water, twice with alcohol, and then dried.
[0051] The morphology, phase and electrochemical characteristics of the manganese-nickel metal organic framework heterogeneous nanosheets prepared in Example 2 of the present invention were performed. Fig.10 , Fig.10 This is a scanning electron microscope photo of the manganese-nickel metal organic framework heterogeneous nanosheet prepared in Example 4 of the present invention. Fig.10It can be seen that the size and thickness of the prepared Mn-Ni metal-organic framework nanosheets are very uniform. Fig.11 , Fig.11 This is the X-ray diffraction pattern of the manganese-nickel metal organic framework heterostructure nanosheet prepared in Example 4 of the present invention. It can be seen that the diffraction peak of the prepared product is significantly offset compared with that of Ni MOF. Fig.12 , Fig.12 The manganese-nickel metal organic framework heterostructure nanosheet prepared in Example 4 of the present invention is used as a cathode material for a zinc ion battery when the current density is 4 A cm -2 The cycling performance diagram of the prepared Mn-Ni metal organic framework heterostructure nanosheet electrode is 0.0900 mAh cm -2 The coulombic efficiency can reach 90.0%, and the capacity is 0.0622 mAh cm after 600 cycles. -2 .
[0052] The first cycle capacity and the capacity after 600 cycles of the bimetallic organic frame heterostructure nanosheet electrodes obtained in the above Examples 1 to 4 are both excellent, and the coulombic efficiency is comparable. The first cycle capacity of the bimetallic organic frame heterostructure nanosheet electrodes obtained in Examples 1 to 3 is higher than that of Example 4, especially the first cycle capacity and the capacity after 600 cycles of the bimetallic organic frame heterostructure nanosheet electrodes obtained in Example 1 are significantly better than those in Example 4.
[0053] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A zinc ion battery cathode material, characterized in that It includes nickel metal organic framework nanosheets and transition metals coated on the nickel metal organic framework nanosheets; The transition metal is selected from one or more of Cr, Zn, Co, Cu, Fe or Mn.
2. The zinc ion battery cathode material according to claim 1, wherein The nickel metal organic framework nanosheet is a Ni MOF nanosheet, and the ligand of the Ni MOF nanosheet is a carboxylic acid-containing ligand.
3. The zinc ion battery cathode material according to claim 1, wherein The molar ratio of nickel to the transition metal in the nickel metal organic framework nanosheet is (0.5-10):
1.
4. A method for preparing a zinc ion battery cathode material, characterized in that: The following steps are involved: A soluble transition metal salt, a nickel metal organic framework nanosheet, N,N-dimethylformamide and an alcohol are heated to react to obtain a zinc ion battery cathode material; The soluble transition metal salt is selected from one or more of soluble Cr salt, soluble Zn salt, soluble Co salt, soluble Cu salt, soluble Fe salt or soluble Mn salt.
5. The preparation method of zinc ion battery cathode material according to claim 4, wherein The nickel metal organic framework nanosheet is a Ni MOF nanosheet, and the ligand of the Ni MOF nanosheet is a carboxylic acid-containing ligand.
6. The preparation method of zinc ion battery cathode material according to claim 4, wherein The molar ratio of nickel in the nickel organic metal framework nanosheet to the transition metal in the soluble transition metal salt is (0.5~5):
1.
7. The preparation method of zinc ion battery cathode material according to claim 4, wherein The volume ratio of N,N-dimethylformamide to alcohol is (1-10):1; The concentration of the nickel metal organic framework nanosheets is 0.3 mg / mL to 3 mg / mL.
8. The preparation method of zinc ion battery cathode material according to claim 4, wherein The temperature of the heating reaction is 50° C. to 260° C., and the time of the heating reaction is 0.5 h to 50 h.
9. A cathode, characterized in that: It includes a current collector and an active component disposed on the current collector; The active component is the zinc ion battery cathode material described in any one of claims 1 to 3 or the zinc ion battery cathode material obtained by the preparation method described in any one of claims 4 to 8.
10. A zinc ion battery, characterized in that: It includes a cathode, an anode and an electrolyte; The cathode is the cathode according to claim 9.
Citation Information
Cited By
Metal organic framework material as well as preparation method and application thereof
CN120944123A